STABILITY OF KETOPROFEN COATED BY CHITOSAN-GUAR GUM GEL - Purwantiningsih Sugita; Bambang Srijanto; Budi Arifin; Ellin Vina Setyowati (Universitas Gadjah Mada, 2009)
The coating stability of ketoprofen by chitosan-guar gum gel has been studied. Into 228.6 mL of 1.75% (w/v) chitosan solution in 1% (v/v) acetic acid, 38.1 mL of guar gum (gg) solution was added with concentration variation of 0.35, 0.55, and 0.75% (w/v) for ketoprofen microcapsules, and stirred with magnetic stirrer until homogenous. Afterwards, 7.62 mL of glutaraldehyde (glu) was added slowly under stirring, with concentrations varied: 3, 3.5, and 4% (v/v). All mixtures were shaked for 20 min for homogenization. Into each microcapsule mixture for ketoprofen, a solution of 2 g of ketoprofen in 250 mL of 96% ethanol was added. Every mixture was then added with 5 mL of 2% Tween-80 and stirred with magnetic stirrer for an hour at room temperature. Conversion of suspension into fine powders/granules (microcapsules) was done by using spray dryer. Every microcapsule formula was packed into capsules, as much as 100 g per capsule. The capsules were contained in 100-mL dark bottles and the bottles were kept in climatic chamber at (40 ± 2) °C and RH (75 ± 5) % for 3 months. The microcapsule stabilities were tested chemically and physically. The result showed that formulation of ketoprofen preparation composed of 1.75% (w/v) chitosan, 0.35% (w/v) gg, and 3.50% (v/v) glu, was relatively the best, with ketoprofen percentage left in microcapsule after 3 months, degradation rate constant, and shelf life of 80.33%, 0.0351 % week-1, and 18.92 months, respectively. Reaction kinetic model for this formula followed Prout-Tompkins equation and the degradation of ketoprofen was seem to follow autocatalytic reaction mechanism controlled by the formation and growth of reaction core.